2014
DOI: 10.3758/s13414-014-0653-z
|View full text |Cite
|
Sign up to set email alerts
|

Expertise for upright faces improves the precision but not the capacity of visual working memory

Abstract: Considerable research has focused on how basic visual features are maintained in working memory, but little is currently known about the precision or capacity of visual working memory for complex objects. How precisely can an object be remembered, and to what extent might familiarity or perceptual expertise contribute to working memory performance? To address these questions, we developed a set of computer-generated face stimuli that varied continuously along the dimensions of age and gender, and we probed par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 47 publications
8
56
2
Order By: Relevance
“…The results were consistent with the effect being an increase in precision, in that the effect of recognisability was found for small (WC) but not large (CC) changes. This finding mirrors the perceptual expertise advantage for VSTM of faces (Curby and Gauthier 2007;Scolari et al 2008;Curby et al 2009;Lorenc et al 2014), but extends it across multiple object categories.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The results were consistent with the effect being an increase in precision, in that the effect of recognisability was found for small (WC) but not large (CC) changes. This finding mirrors the perceptual expertise advantage for VSTM of faces (Curby and Gauthier 2007;Scolari et al 2008;Curby et al 2009;Lorenc et al 2014), but extends it across multiple object categories.…”
Section: Discussionsupporting
confidence: 66%
“…We also extend it to another measure of precision, obtained from modelling the distribution of responses in a continuous report paradigm. This confirmed that recognisable objects are remembered with greater precision but with no advantage in the number of items that can be retained, similar to an advantage seen for upright faces (Lorenc et al 2014). This advantage in precision may be explained by a wider representational space for recognisable objects (Scolari et al 2008;Brady et al 2016).This raised the question as to the neural mechanisms that support VSTM for complex objects and that underlie a behavioural precision advantage for recognisability.…”
Section: Greater Precision For Recognisable Complex Objects In Vstmsupporting
confidence: 55%
“…Lorenc and colleagues (2014) use memory for faces to make this point. Their observers saw a sequence of faces, each in its own specific location and were then probed for one of those faces.…”
Section: Properties Of Working Memorymentioning
confidence: 99%
“…The authors took this as evidence that expertise enhances the precision of working memory representation but not capacity in terms of the number of "slots." The number of items represented should be independent of expertise, but unfamiliar items are represented less precisely than familiar ones (Lorenc et al, 2014).…”
Section: Introductionmentioning
confidence: 99%